2019
DOI: 10.1080/08870446.2019.1626125
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and support needs of informal caregivers of people with multimorbidity: a scoping literature review

Abstract: Experiences and support needs of informal caregivers of people with multimorbidity: a scoping literature review Objective: Describe and synthesise existing published research on the experiences and support needs of informal caregivers of people with multimorbidity.Design: Scoping literature review. Primary database and secondary searches for qualitative and/or quantitative English-language research with an explicit focus on informal carers of people with multimorbidity (no date restrictions). Quality appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 92 publications
4
55
0
Order By: Relevance
“…Poor communication in the health-care system, generally (not just during care transitions), is a common problem expressed by many patients and their caregivers, 41 typically those who have multiple chronic conditions, 42 require significant health care and interact with various care providers across settings. 43 Care transitions, in particular, are a heightened time of vulnerability for patients and their caregivers.…”
Section: Communicating Uncertaintymentioning
confidence: 99%
“…Poor communication in the health-care system, generally (not just during care transitions), is a common problem expressed by many patients and their caregivers, 41 typically those who have multiple chronic conditions, 42 require significant health care and interact with various care providers across settings. 43 Care transitions, in particular, are a heightened time of vulnerability for patients and their caregivers.…”
Section: Communicating Uncertaintymentioning
confidence: 99%
“…19,21,22 A recent scoping literature review of 27 quantitative and qualitative studies of the experiences of caregivers of adults with multimorbidity found that caregivers carried out a range of time-consuming tasks to support the care recipient such as providing physical care, stimulating the older adult, and scheduling and attending medical appointments. 23 The additional burden associated with these tasks often resulted in increased stress, anxiety, and depression. 23 The review found that caregivers were uncertain about how to manage the care recipients' symptoms and conditions and needed more information from health care providers on how to recognize and manage symptoms or side effects.…”
Section: Introductionmentioning
confidence: 99%
“…23 The additional burden associated with these tasks often resulted in increased stress, anxiety, and depression. 23 The review found that caregivers were uncertain about how to manage the care recipients' symptoms and conditions and needed more information from health care providers on how to recognize and manage symptoms or side effects. While some studies included in the review identified positive outcomes of caregiving (e.g., enhanced learning and empathy), negative outcomes were commonly described such as lack of time for self-care and decreased social networks and supports.…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, it would be important to evaluate unmet needs in different stages of the care provision since caregivers’ needs can change over illness and ageing trajectories. Understanding the kind of needs that emerge throughout time, and how they vary according to the intensity of care and dependency level, could inform the design and adequacy of interventions in the care‐giving continuum at such advanced ages (Price et al., 2020).…”
Section: Discussionmentioning
confidence: 99%